SUBSTANTIATION OF TRANSPORTATION PARAMETERS ON UR-BAN AND LONG-DISTANCE ROUTES OF DNIPROPETROVSK RE-GION - Lesnikova, I.; Khalipova, N.; Malenko, Y.; Zborshchenko, A. (Systems and Technologies, 2021)
The article is devoted to the analysis of the state of passenger transportation on the basis of the existing transport network for cities in the Dnipropetrovsk re-gion, the definition of models and methods for calculating the matrix of passenger transport correspondence. The problem of calculations of the correspondence ma-trix for two formed city and intercity transport networks of the Dnepropetrovsk re-gion is solved. Based on the obtained results, possible models for passenger transport routes within the region are proposed. The relevance of the approaches presented in this article is to substantiate the parameters of transportation on urban and interurban routes of Dnipropetrovsk region, which is one of the largest industrial, economic, cultural and historical cen-ters of the country and has a high population density - 100 people / km2. Currently, with the increase of the population of megapolises, obviously, the load on their transport systems is growing. In each of them, a fundamentally im-portant task is to monitor and regulate traffic flows, i.e. movements within this sys-tem. Mathematically, the movement of passengers within the transport system is described by a matrix of correspondence. The article calculates two matrices of passenger correspondence by gravity method according to the input data. The first - the cities of Dnipropetrovsk region with the largest population, the second - the settlements of Dnipropetrovsk region, which are located around the city of Dnipro and have a small population. The analysis of the results showed that the number of moving working population, is directly proportional to the total population of the city, village, their area and re-gional significance. The more developed industry, economy, science, culture, the greater the population moves between important cities for the region. The largest settlements of the Dnipropetrovsk region, between which there is a transport con-nection are the Dnipro, Kryvyi Rih, Kamianske, Nikopol and Pavlograd; the smallest - Spaske, Loboykivka, Chaplynka. The routing problem is solved under the conditions of correspondence of the initial value of the labor capacity of the districts and the labor capacity obtained as a result of the distribution of correspondence according to the gravitational model. This approach can be useful in determining the weight of individual settlements of the region when designing road and traffic infrastructure, repairing roads and planning a route connection between cities and villages. The results of the study are of scientific and practical significance, because they can be used in the design and improvement of transport infrastructure of Dnipropetrovsk region, certain categories of roads in the planning of bus and rail services between cities and villages. Substantiated parameters of urban and inter-urban passenger traffic make it possible to determine the time of transportation, the number of bus trips and the required number of buses and their dimensions per day. It is desirable to establish the end points of the routes between the largest cit-ies, because this is the connection with the largest number of displaced people. However, the location of small settlements should be considedred to meet the transport needs of the entire population of Dnipropetrovsk region with minimal costs and maximum profits.